Investigating the Phase-Morphology of PLLA-PCL Multiblock Copolymer / PDLA Blends Cross-linked Using Stereocomplexation. (2020) - Izraylit, Victor; Gould, Oliver E. C.; Kratz, Karl; Lendlein, Andreas
ABSTRACT: The macroscale function of multicomponent polymeric materials is dependent on their phase-morphology. Here, we investigate the morphological structure of a multiblock copolymer consisting of poly(L-lactide) and poly(ε-caprolactone) segments (PLLA-PCL), physically cross-linked by stereocomplexation with a low molecular weight poly(D-lactide) oligomer (PDLA). The effects of blend composition and PLLA-PCL molecular structure on the morphology are elucidated by AFM, TEM and SAXS. We identify the formation of a lattice pattern, composed of PLA domains within a PCL matrix, with an average domain spacing d0 = 12 – 19 nm. The size of the PLA domains were found to be proportional to the block length of the PCL segment of the copolymer and inversely proportional to the PDLA content of the blend. Changing the PLLA-PCL / PDLA ratio caused a shift in the melt transition Tm attributed to the PLA stereocomplex crystallites, indicating partial amorphous phase dilution of the PLA and PCL components within the semicrystalline material. By elucidating the phase structure and thermal character of multifunctional PLLA-PCL / PDLA blends, we illustrate how composition affects the internal structure and thermal properties of multicomponent polymeric materials. This study should facilitate the more effective incorporation of a variety of polymeric structural units capable of stimuli responsive phase transitions, where an understanding the phase-morphology of each component will enable the production of multifunctional soft-actuators with enhanced performance.